Secondary battery and electronic device

By using conductive carbon black, carbon nanotubes or sheet-shaped graphene in the positive electrode sheet of lithium-ion battery, a stable conductive network is formed, which solves the problem of lower conductivity after thickening of the electrode sheet, and achieves better charge and discharge performance and energy density.

CN120164953APending Publication Date: 2025-06-17NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510400742.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

After the electrode sheet is thickened, the ionic conductivity and electron conductivity are significantly reduced, resulting in a decrease in charge and discharge performance, especially the charging time is significantly deteriorated under fast charging conditions.

Method used

By using conductive agent combinations such as conductive carbon black, carbon nanotubes or sheet-shaped graphene in the positive electrode sheet, the contact sites between the particles of the positive electrode active material are improved to form a stable conductive network, thereby improving the ionic conductivity and electron conductivity.

Benefits of technology

The charging and discharging performance of the thick positive electrode sheet is improved, the charging time is shortened, the discharge capacity retention rate is improved, and the energy density of the secondary battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120164953A_ABST
    Figure CN120164953A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and an electronic device. The secondary battery comprises a positive pole piece, an isolating membrane and a negative pole piece, the positive pole piece comprises a positive current collector and a positive material layer arranged on at least one surface of the positive current collector, and the negative pole piece comprises a negative current collector and a negative material layer arranged on at least one surface of the negative current collector; the thickness of the positive electrode material layer is H1 [mu] m, and 22 < = H1 < = 110; the positive electrode material layer comprises a positive electrode active material, a positive electrode binder and a positive electrode conductive agent, and the positive electrode conductive agent comprises conductive carbon black and at least one of a carbon nanotube or flake graphene; the particle size Dv50 of the conductive carbon black is D1 [mu] m, 0.5 < = D1 < = 20. Through the arrangement, the charging and discharging performance of the secondary battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technologies, and particularly to a secondary battery and an electronic device. Background Art

[0002] Secondary batteries, such as lithium-ion batteries, are widely used in products such as digital electronic products, energy storage, drones, power tools, and electric vehicles due to their characteristics such as high energy density, long cycle life, high safety, and fast charging ability. With the increasing demand for thinner and lighter products, there is a need for secondary batteries with higher and higher energy density.

[0003] Conventional methods for increasing energy density include increasing the specific capacity of the positive / negative active materials, increasing the charging voltage platform, etc. Increasing the thickness of the electrode sheet and the surface coating density of the electrode sheet is one of the means in the industry to increase energy density. However, after the thickness of the electrode sheet increases, it means that the lithium-ion transmission path increases, and the ionic conductivity and electronic conductivity will be significantly reduced, resulting in a decrease in the rate discharge capacity of the secondary battery. For secondary batteries of the fast charging (actual charging rate > 1C) type, the thickening of the electrode sheet will lead to a significant deterioration of the charging time. Therefore, how to improve the ionic conductivity and electronic conductivity of the thick electrode sheet and improve the charge and discharge performance of the secondary battery with the thick electrode sheet will be the most urgent problem to be solved for the thick electrode sheet to increase the energy density. Summary of the Invention

[0004] The purpose of the present application is to provide a secondary battery and an electronic device to improve the charge and discharge performance of the secondary battery.

[0005] It should be noted that in the summary of the invention of the present application, a lithium-ion battery is used as an example of the secondary battery to explain the present application, but the secondary battery of the present application is not limited to the lithium-ion battery. The specific technical solutions are as follows:

[0006] The first aspect of the present application provides a secondary battery, which includes a positive electrode plate, a separator, and a negative electrode plate. The positive electrode plate includes a positive current collector and a positive electrode material layer provided on at least one surface of the positive current collector. The negative electrode plate includes a negative current collector and a negative electrode material layer provided on at least one surface of the negative current collector. The thickness of the positive electrode material layer is H1 μm, where 22 ≤ H1 ≤ 110. The positive electrode material layer includes a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent. The positive electrode conductive agent includes conductive carbon black and at least one of carbon nanotubes or flaky graphene. The particle size Dv50 of the conductive carbon black is D1 μm, where 0.5 ≤ D1 ≤ 20. When the thickness of the positive electrode material layer in the secondary battery of the present application is within the scope of the present application, by selecting conductive carbon black with a particle size Dv50 within the scope of the present application, the zero-dimensional conductive carbon black has a high coverage on the surface of the positive electrode active material, so as to improve the conductivity. The use of one-dimensional carbon nanotubes is beneficial to connect the particles of the positive electrode active material in series, maintain the network conductive network between the particles, and reduce the probability of damage to the conductive network caused by the expansion of the positive electrode plate during the charge and discharge cycle of the secondary battery. The use of two-dimensional flaky graphene can enable the particles of the positive electrode active material to achieve surface contact, increase the contact sites, improve the conductivity, and the flaky graphene can provide slippage between the particles of the positive electrode active material, reducing the probability of brittle fracture of the thick positive electrode plate. In the thick positive electrode plate of the present application, using at least one of conductive carbon black and carbon nanotubes or flaky graphene in combination can increase the contact sites between the particles of the positive electrode active material, form a conductive network between the particles of the positive electrode active material, is beneficial to constructing a stable conductive network in the positive electrode material layer, improve the ionic conductivity and electronic conductivity of the positive electrode plate, and thus improve the charge and discharge performance of the secondary battery. The use of the thick positive electrode plate can provide a high capacity for the secondary battery, enabling the secondary battery to have a high energy density.

[0007] In some embodiments of the present application, the specific surface area of the conductive carbon black is S m 2 / g, where 200 ≤ S ≤ 2100. Controlling the specific surface area of the conductive carbon black within the above range is beneficial to forming a stable conductive network on the surface of each particle of the positive electrode active material and improving the charge and discharge performance of the secondary battery.

[0008] In some embodiments of the present application, the secondary battery satisfies at least one of the following characteristics: (1) the specific surface area of the conductive carbon black is S m 2 / g, where 600 ≤ S ≤ 1800; (2) 1.5 ≤ D1 ≤ 10. It is beneficial to improve the charge and discharge performance of the secondary battery.

[0009] In some embodiments of the present application, the secondary battery satisfies at least one of the following characteristics: (1) the specific surface area of the conductive carbon black is S m 2 / g, 1200 ≤ S ≤ 1800; (2) The thickness of the positive electrode material layer is H1 μm, 45 ≤ H1 ≤ 100. This is beneficial to improving the charge and discharge performance and energy density of the secondary battery.

[0010] In some embodiments of the present application, the thickness of the positive electrode material layer is 70 μm to 100 μm, which can further take into account better performance in the full charge duration test, energy density test, and capacity retention rate test.

[0011] In some embodiments of the present application, the coating surface density of the positive electrode material layer is C1 mg / cm 2 , 10 ≤ C1 ≤ 55. By adjusting the coating surface density of the positive electrode material layer within the above range, on the basis of good charge and discharge performance, the secondary battery also has a high energy density.

[0012] In some embodiments of the present application, the negative electrode sheet satisfies at least one of the following characteristics: (1) The thickness of the negative electrode material layer is H2 μm, 10 ≤ H2 ≤ 140; (2) The coating surface density of the negative electrode material layer is C2 mg / cm 2 , 2.5 ≤ C2 ≤ 35. On the basis of good charge and discharge performance, the secondary battery also has a high energy density.

[0013] In some embodiments of the present application, the carbon nanotubes satisfy at least one of the following characteristics: (1) The length of the carbon nanotubes is L1 nm, 100 ≤ L1 ≤ 6000; (2) The diameter of the carbon nanotubes is D2 nm, 8 ≤ D2 ≤ 18; (3) The aspect ratio L1 / D2 of the carbon nanotubes satisfies: 25 ≤ L1 / D2 ≤ 300. This is beneficial for the carbon nanotubes to connect the particles of the positive electrode active material in series, construct a stable conductive network in the positive electrode material layer, improve the ionic conductivity and electronic conductivity of the positive electrode sheet, and thus improve the charge and discharge performance of the secondary battery.

[0014] In some embodiments of the present application, the sheet diameter of the flaky graphene is 5 μm to 15 μm. By adjusting the sheet diameter of the flaky graphene within the above range, it is beneficial to achieve surface contact between the particles of the positive electrode active material and improve the charge and discharge performance of the secondary battery.

[0015] In some embodiments of the present application, the weight-average molecular weight of the positive electrode binder is Mw, and the number-average molecular weight of the positive electrode binder is Mn. The relationship between Mw and Mn satisfies: 1.5 ≤ Mw / Mn ≤ 3, and 800,000 ≤ Mw ≤ 1,200,000. By regulating Mw / Mn and Mw within the above ranges, the molecular weight distribution of the positive electrode binder is relatively concentrated, which can endow the positive electrode binder with good binding properties, reduce the amount of the positive electrode binder in the positive electrode material layer, and reduce the coating of the positive electrode binder on the positive electrode active material, so as to more fully exert the capacity of the positive electrode active material, thereby improving the energy density of the secondary battery. It also reduces the probability of brittle fracture of the positive electrode sheet, improves the manufacturing yield of the positive electrode sheet, and reduces the production cost of the secondary battery.

[0016] In some embodiments of the present application, based on the mass of the positive electrode material layer, the mass percentage content of the positive electrode conductive agent is W1%, the mass percentage content of the positive electrode binder is W2%, and the mass percentage content of the positive electrode active material is W3%. 0.2 ≤ W1 ≤ 2.0, 0.5 ≤ W2 ≤ 1.5, 96.5 ≤ W3 ≤ 99.1. In some embodiments of the present application, the secondary battery satisfies at least one of the following characteristics: (1) 0.5 ≤ W1 ≤ 1.0; (2) 0.7 ≤ W2 ≤ 1.5; (3) 97.7 ≤ W3 ≤ 98.8. By regulating the mass percentage contents of the positive electrode conductive agent, the positive electrode binder, and the positive electrode active material within the above ranges, it is beneficial to prepare a positive electrode material layer with good adhesion, conductivity, and high capacity.

[0017] In some embodiments of the present application, the positive electrode conductive agent satisfies at least one of the following characteristics: (1) based on the mass of the positive electrode material layer, the mass percentage content of conductive carbon black is Y1%, 0.1 ≤ Y1 ≤ 1; (2) based on the mass of the positive electrode material layer, the mass percentage content of carbon nanotubes is Y2%, 0.1 ≤ Y2 ≤ 0.5; (3) based on the mass of the positive electrode material layer, the mass percentage content of flaky graphene is Y3%, 0.1 ≤ Y3 ≤ 0.5. The positive electrode sheet has high ionic conductivity and electronic conductivity, thereby improving the charge and discharge performance of the secondary battery.

[0018] In some embodiments of the present application, the particle size Dv99 of the positive electrode active material is D3 μm, and the relationship between H1 and D3 satisfies: 0.8 ≤ H1 / D3 ≤ 3.5. By regulating H1 / D3 within the above ranges, the secondary battery has good charge and discharge performance and high energy density.

[0019] In some embodiments of the present application, the positive electrode sheet satisfies at least one of the following characteristics: (1) 1.0 ≤ H1 / D3 ≤ 2.0; (2) 20 ≤ D3 ≤ 55; (3) the tap density of the positive electrode sheet is PD g / cm 3, 3.8 ≤ PD ≤ 4.45, preferably, 3.95 ≤ PD ≤ 4.25. This enables the secondary battery to have good charge and discharge performance and a relatively high energy density.

[0020] In some embodiments of the present application, the positive electrode tab further includes a bottom coating disposed between the positive electrode current collector and the positive electrode material layer. The bottom coating includes inorganic particles and a bottom coating binder; the thickness of the bottom coating is H3 μm, and H3 and H1 satisfy: 10 ≤ H1 / H3 ≤ 110, 0.2 ≤ H3 ≤ 5.0. Further providing a bottom coating in the positive electrode tab and controlling the thickness of the bottom coating within the above range is beneficial to improving the adhesion and hardness of the positive electrode tab, enabling the secondary battery to have good safety performance on the basis of good charge and discharge performance and a relatively high energy density.

[0021] In some embodiments of the present application, 0.5 ≤ H3 ≤ 2.5. Controlling the thickness of the bottom coating within the above range can further improve the energy density of the secondary battery on the basis of good charge and discharge performance and safety performance.

[0022] The second aspect of the present application provides an electronic device, which includes the secondary battery described in any of the foregoing embodiments. Therefore, the electronic device has good usability.

[0023] Advantages of the present application:

[0024] The present application provides a secondary battery and an electronic device. The secondary battery includes a positive electrode tab, a separator, and a negative electrode tab. The positive electrode tab includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector. The negative electrode tab includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; the thickness of the positive electrode material layer is H1 μm, 22 ≤ H1 ≤ 110; the positive electrode material layer includes a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent. The positive electrode conductive agent includes conductive carbon black and at least one of carbon nanotubes or flaky graphene; the particle size Dv50 of the conductive carbon black is D1 μm, 0.5 ≤ D1 ≤ 20. In the thick positive electrode tab, using the conductive agent combination with the above characteristics can increase the contact sites between the positive electrode active material particles, form a conductive network between the positive electrode active material particles, be beneficial to constructing a stable conductive network in the positive electrode material layer, improve the ionic conductivity and electronic conductivity of the positive electrode tab, and thus improve the charge and discharge performance of the secondary battery.

[0025] Of course, implementing any product or method of the present application does not necessarily require achieving all the above-mentioned advantages simultaneously. Brief Description of the Drawings

[0026] To more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of the present application. For those of ordinary skill in the art, other embodiments can also be obtained based on these drawings.

[0027] Figure 1 Schematic cross-sectional structure diagram of the positive electrode sheet of an implementation solution of the present application along its thickness direction and length direction;

[0028] Figure 2 Schematic cross-sectional structure diagram of the positive electrode sheet of another implementation solution of the present application along its thickness direction and length direction.

[0029] Reference numerals:

[0030] 100 - positive electrode sheet, 101 - positive current collector, 10 - positive electrode material layer, 20 - bottom coating. Specific implementation manners

[0031] The following will clearly and completely describe the technical solutions in the present application in conjunction with the embodiments of the present application and the drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0032] It should be noted that in the specific implementation manners of the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application. However, the secondary battery of the present application is not limited to lithium-ion batteries.

[0033] The first aspect of the present application provides a secondary battery, which includes a positive electrode sheet, a separator, and a negative electrode sheet. The positive electrode sheet includes a positive current collector and a positive electrode material layer provided on at least one surface of the positive current collector. The negative electrode sheet includes a negative current collector and a negative electrode material layer provided on at least one surface of the negative current collector. The thickness of the positive electrode material layer is H1 μm, and 22 ≤ H1 ≤ 110. The positive electrode material layer includes a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent. The positive electrode conductive agent includes conductive carbon black and at least one of carbon nanotubes or flaky graphene. The particle size Dv50 of the conductive carbon black is D1 μm, and 0.5 ≤ D1 ≤ 20.

[0034] For the convenience of understanding, in this application, the self-length direction of the positive electrode plate is defined as X, and the self-thickness direction is defined as Z. It should be understood that the above definitions of directions are for the convenience of describing the purpose of this application, and the directions defined in this application can be understood according to the relative positions of the drawings and the actual product elements. Moreover, the length direction and thickness direction of the positive current collector, the positive electrode material layer, and the bottom coating are the same as those of the positive electrode plate. The above "positive electrode material layer provided on at least one surface of the positive current collector" means that the positive electrode material layer is provided on one surface or two surfaces of the positive current collector. The above "negative electrode material layer provided on at least one surface of the negative current collector" means that the negative electrode material layer is provided on one surface or two surfaces of the negative current collector. As Figure 1 shown, the positive electrode plate 100 includes a positive current collector 101 and a positive electrode material layer 10, and the positive electrode material layer 10 is provided on two surfaces of the positive current collector 101. Of course, it can be understood that in some embodiments of this application, the positive electrode material layer 10 is provided on one surface of the positive current collector 101.

[0035] For example, H1 is 22, 40, 45, 50, 60, 70, 80, 85, 92, 100, 103, 110 or any value between any two of the above numerical ranges. If H1 is less than 22, the thickness of the positive electrode material layer is too small, the capacity provided by the positive electrode active material for the secondary battery is too small, and the energy density of the secondary battery is too small; if H1 is greater than 110, the thickness of the positive electrode material layer is too large, the polarization increases due to the increased lithium ion transmission path, the ionic conductivity and electronic conductivity of the positive electrode plate decrease, the charging speed of the secondary battery decreases, the rate performance deteriorates, the cycle capacity decays severely, and the volume of the secondary battery will also increase, and the increase in the volume of the secondary battery will result in a loss of energy density.

[0036] For example, D1 is 0.5, 1.5, 3, 5, 6, 8, 10, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any value between any two of the above numerical ranges. If D1 is less than 0.5, the particle size of the conductive carbon black is too small, the conductive carbon black particles are prone to agglomeration, and the distribution in the positive electrode material layer is uneven, affecting the conductive effect; if D1 is greater than 20, the particle size of the conductive carbon black is too large, and the coverage of the conductive carbon black on the surface of the positive electrode active material is too low to achieve the effect of improving the conductive performance.

[0037] Generally speaking, when the thickness of the positive electrode material layer in the secondary battery of the present application is within the scope of the present application, by selecting conductive carbon black with a Dv50 particle size within the scope of the present application, the zero-dimensional conductive carbon black has a high coverage on the surface of the positive electrode active material, so as to improve the conductivity. The use of one-dimensional carbon nanotubes is conducive to connecting the particles of the positive electrode active material in series, maintaining the network conductive network between the particles, and reducing the probability of damage to the conductive network during the charge and discharge cycle of the secondary battery. The use of two-dimensional flaky graphene enables surface contact between the particles of the positive electrode active material, increases the contact sites, improves the conductivity, and the flaky graphene can provide slippage between the particles of the positive electrode active material, reducing the probability of brittle fracture of the thick positive electrode sheet. In the thick positive electrode sheet of the present application, the combined use of at least one of conductive carbon black and carbon nanotubes or flaky graphene can increase the contact sites between the particles of the positive electrode active material, form a conductive network between the particles of the positive electrode active material, is conducive to constructing a stable conductive network in the positive electrode material layer, improving the ionic conductivity and electronic conductivity of the positive electrode sheet, facilitating the capacity utilization of the positive electrode sheet, and thus improving the charge and discharge performance of the secondary battery. The use of the thick positive electrode sheet can provide a higher capacity for the secondary battery and endow the secondary battery with a higher energy density.

[0038] Exemplarily, in one embodiment, the positive electrode conductive agent includes conductive carbon black and carbon nanotubes. The conductive carbon black particles of the present application have a high coverage on the surface of the positive electrode active material, can reduce the reaction activation energy, and are conducive to improving the conductive effect on the surface of the positive electrode active material particles. The carbon nanotubes connect the particles of the positive electrode active material in series, maintaining the network conductive network between the particles. The combined use of conductive carbon black and carbon nanotubes can construct a stable and effective conductive network in the positive electrode material layer, which is conducive to improving the ionic conductivity and electronic conductivity of the positive electrode sheet and improving the charge and discharge performance of the secondary battery. In another embodiment, the positive electrode conductive agent includes conductive carbon black and flaky graphene. The conductive carbon black particles of the present application have a high coverage on the surface of the positive electrode active material, can reduce the reaction activation energy, and are conducive to improving the conductive effect on the surface of the positive electrode active material particles. The use of two-dimensional flaky graphene enables surface contact between the particles of the positive electrode active material, increases the contact sites, and improves the conductivity. The combined use of conductive carbon black and flaky graphene can improve the compaction density of the positive electrode sheet on the basis of improving the conductive performance, providing a higher energy density and kinetic performance for the secondary battery. In yet another embodiment, the positive electrode conductive agent includes conductive carbon black, carbon nanotubes and flaky graphene. The combined use of the above three substances realizes the combination of points, lines and surfaces, forming a good and stable conductive network between the particles of the positive electrode active material, which is conducive to further improving the ionic conductivity and electronic conductivity of the positive electrode sheet, and thus improving the charge and discharge performance of the secondary battery.

[0039] In some embodiments of the present application, the thickness of the positive electrode material layer is H1 μm, where 45 ≤ H1 ≤ 100. For example, H1 is 45, 50, 60, 70, 80, 85, 92, 100, or any value between any two of the above numerical ranges. Controlling the thickness of the positive electrode material layer within the above range is conducive to having more positive electrode active material in the positive electrode material layer, providing a higher capacity for the secondary battery. In this way, on the basis of good charge and discharge performance, the secondary battery also has a higher energy density.

[0040] In some embodiments of the present application, the Dv50 particle size of the conductive carbon black is D1 μm, where 1.5 ≤ D1 ≤ 10. For example, D1 is 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, or any value between any two of the above numerical ranges. Controlling the Dv50 particle size of the conductive carbon black within the above range results in a lower probability of agglomeration of the conductive carbon black, which is conducive to the uniform distribution of the conductive carbon black in the positive electrode material layer. The conductive carbon black can have a higher specific surface area to have a higher coverage on the surface of the positive electrode active material, reducing the reaction activation energy. In this way, it is conducive to the formation of a stable conductive network by the conductive carbon black on the surface of each particle of the positive electrode active material, exerting its conductive performance, improving the ionic conductivity and electronic conductivity of the positive electrode sheet, and thus being conducive to improving the charge and discharge performance of the secondary battery.

[0041] In the present application, the "Dv50 particle size of the conductive carbon black" refers to the particle size at which the cumulative volume of the primary particles of the conductive carbon black reaches 50% starting from the small particle size side in the particle size distribution based on volume.

[0042] In some embodiments of the present application, the specific surface area of the conductive carbon black is S m 2 / g, where 200 ≤ S ≤ 2100. For example, S is 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 2000, 2100, or any value between any two of the above numerical ranges. Controlling the specific surface area of the conductive carbon black within the above range, the conductive carbon black particles have a relatively large specific surface area, can have a higher coverage on the surface of the positive electrode active material, are conducive to the formation of a stable conductive network by the conductive carbon black on the surface of each particle of the positive electrode active material, exerting its conductive performance, improving the ionic conductivity and electronic conductivity of the positive electrode sheet, and thus being conducive to improving the charge and discharge performance of the secondary battery.

[0043] In some embodiments of the present application, the specific surface area of the conductive carbon black is S m 2 / g, 600 ≤ S ≤ 1800. For example, S is 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, or any value between any two of the above numerical ranges. By controlling the specific surface area of the conductive carbon black within the above range, the conductive carbon black particles have a larger specific surface area, can have a higher coverage on the surface of the positive electrode active material, and are more conducive to forming a stable conductive network on the surface of each particle of the positive electrode active material, exerting its conductive performance, improving the ionic conductivity and electronic conductivity of the positive electrode sheet, and thus being conducive to further improving the charge and discharge performance of the secondary battery.

[0044] In some embodiments of the present application, the specific surface area of the conductive carbon black is S m 2 / g, 1200 ≤ S ≤ 1800. For example, S is 1200, 1300, 1400, 1500, 1600, 1700, 1800, or any value between any two of the above numerical ranges. By controlling the specific surface area of the conductive carbon black within the above range, the specific surface area of the conductive carbon black particles is further increased, can further have a higher coverage on the surface of the positive electrode active material, and is more conducive to forming a stable conductive network on the surface of each particle of the positive electrode active material, exerting its conductive performance, improving the ionic conductivity and electronic conductivity of the positive electrode sheet, and thus being conducive to further improving the charge and discharge performance of the secondary battery.

[0045] The present application has no particular limitation on the regulation method of the particle size Dv50 of the conductive carbon black, as long as the purpose of the present application can be achieved. For example, it can be achieved by crushing, mechanical crushing (such as ball milling), and screening. The present application has no particular limitation on the regulation method of the specific surface area of the conductive carbon black, as long as the purpose of the present application can be achieved. Usually, the value of the specific surface area of the conductive carbon black can be adjusted by mechanically crushing (such as ball milling) to change the particle size of the conductive carbon black. When other conditions remain unchanged, prolonging the ball milling time, the particle size of the conductive carbon black decreases, and the specific surface area increases; shortening the ball milling time, the particle size of the conductive carbon black increases, and the specific surface area decreases.

[0046] In some embodiments of the present application, the coating surface density of the positive electrode material layer is C1 mg / cm 2 , 10 ≤ C1 ≤ 55. For example, C1 is 10, 12, 15, 20, 26, 30, 40, 45, 50, 55, or any value between any two of the above numerical ranges. By controlling the coating surface density of the positive electrode material layer within the above range, it is beneficial to make the positive electrode material layer contain more positive electrode active materials without affecting the lithium ion transmission channels and transmission rates, and can provide a higher capacity for the secondary battery. In this way, on the basis of having good charge and discharge performance, the secondary battery also has a higher energy density.

[0047] In some embodiments of the present application, the thickness of the negative electrode material layer is H2 μm, where 10 ≤ H2 ≤ 140. For example, the thickness of the negative electrode material layer is 10 μm, 20 μm, 26 μm, 30 μm, 37 μm, 40 μm, 50 μm, 55 μm, 60 μm, 63 μm, 70 μm, 80 μm, 86 μm, 94 μm, 100 μm, 108 μm, 120 μm, 130 μm, 140 μm, or any value between any two of the above numerical ranges. By controlling the thickness of the negative electrode material layer within the above range, there is a relatively large amount of negative electrode active material in the negative electrode material layer, which can provide more lithium ion insertion and extraction sites for lithium ions, and provide a higher capacity for the secondary battery. In this way, on the basis of having good charge and discharge performance, the secondary battery also has a relatively high energy density.

[0048] In some embodiments of the present application, the coating surface density of the negative electrode material layer is C2 mg / cm 2 , where 2.5 ≤ C2 ≤ 35. For example, C2 is 2.5, 5, 7, 10, 12, 13, 15, 18, 20, 22, 25, 28, 31, 35, or any value between any two of the above numerical ranges. By controlling the coating surface density of the negative electrode material layer within the above range, it is beneficial to contain a relatively large amount of negative electrode active material in the negative electrode material layer to provide more lithium ion insertion and extraction sites for lithium ions without affecting the lithium ion transmission channels and transmission rates, thereby improving the capacity of the secondary battery. In this way, on the basis of having good charge and discharge performance, the secondary battery also has a relatively high energy density.

[0049] In some embodiments of the present application, the length of the carbon nanotubes is L1 nm, where 100 ≤ L1 ≤ 6000. For example, L1 is 100, 200, 500, 700, 1000, 1200, 1500, 2000, 2500, 3000, 3500, 4000, 4600, 5000, 5200, 5400, 6000, or any value between any two of the above numerical ranges. By controlling the length of the carbon nanotubes within the above range, it is beneficial for the carbon nanotubes to connect the particles of the positive electrode active material in series, maintain the network conductive network between the particles, and reduce the probability of damage to the conductive network caused by the expansion of the positive electrode plate during the charge and discharge cycles of the secondary battery. In this way, the use of carbon nanotubes in the positive electrode plate is beneficial to constructing a stable conductive network in the positive electrode material layer, improving the ionic conductivity and electronic conductivity of the positive electrode plate, and thus improving the charge and discharge performance of the secondary battery.

[0050] In some embodiments of the present application, the diameter of the carbon nanotubes is D2 nm, where 8 ≤ D2 ≤ 18. For example, D2 is 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, or any value between any two of the above numerical ranges. By controlling the diameter of the carbon nanotubes within the above range, the probability of the carbon nanotubes breaking due to the expansion of the positive electrode plate is relatively low, which is beneficial to reducing the probability of the conductive network being damaged due to the expansion of the positive electrode plate during the charge and discharge cycles of the secondary battery. In this way, the use of carbon nanotubes in the positive electrode plate is beneficial to constructing a stable conductive network in the positive electrode material layer, improving the ionic conductivity and electronic conductivity of the positive electrode plate, and thus improving the charge and discharge performance of the secondary battery.

[0051] In some embodiments of the present application, the aspect ratio L1 / D2 of the carbon nanotubes satisfies: 25 ≤ L1 / D2 ≤ 300. For example, L1 / D2 is 25, 50, 60, 80, 100, 120, 140, 160, 178, 200, 210, 223, 254, 270, 280, 290, 300, or any value between any two of the above numerical ranges. By controlling the aspect ratio of the carbon nanotubes within the above range, it is beneficial for the carbon nanotubes to connect the particles of the positive electrode active material in series, construct a stable conductive network in the positive electrode material layer, improve the ionic conductivity and electronic conductivity of the positive electrode plate, and thus improve the charge and discharge performance of the secondary battery.

[0052] The present application does not particularly limit the method of controlling the length and diameter of the carbon nanotubes, as long as the purpose of the present application can be achieved. For example, it can be achieved by purchasing commercially available carbon nanotubes and selecting the carbon nanotubes with the required length and diameter in the present application, or it can be achieved by sanding and sieving the commercially available carbon nanotubes after purchase. In some embodiments of the present application, the sheet diameter of the flaky graphene is 5 μm to 15 μm. For example, the sheet diameter of the flaky graphene is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or any value between any two of the above numerical ranges. By controlling the sheet diameter of the flaky graphene within the above range, it is beneficial to achieve surface contact between the particles of the positive electrode active material, increase the contact sites, improve the conductive ability, and thus improve the ionic conductivity and electronic conductivity of the positive electrode plate, and improve the charge and discharge performance of the secondary battery.

[0053] The present application does not particularly limit the method of controlling the sheet diameter of the flaky graphene, as long as the purpose of the present application can be achieved. For example, it can be achieved by purchasing commercially available flaky graphene and selecting the flaky graphene with the required sheet diameter in the present application.

[0054] There is no particular limitation on the number of layers of the sheet-like graphene in this application, as long as the object of this application can be achieved. For example, the number of layers of the sheet-like graphene is from 3 to 30 layers, preferably from 5 to 20 layers, and more preferably from 8 to 12 layers.

[0055] In some embodiments of this application, the weight-average molecular weight of the positive electrode binder is Mw, and the number-average molecular weight of the positive electrode binder is Mn. The relationship between Mw and Mn satisfies: 1.5 ≤ Mw / Mn ≤ 3, and 800,000 ≤ Mw ≤ 1,200,000. For example, Mw / Mn is 1.5, 1.7, 1.8, 2.0, 2.2, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3 or any value between any two of the above numerical ranges. For example, Mw is 800,000, 900,000, 1,000,000, 1,100,000, 1,200,000 or any value between any two of the above numerical ranges. By regulating Mw / Mn and Mw within the above ranges, the molecular weight distribution of the positive electrode binder is relatively concentrated, the probability of agglomeration of more small-molecule binders is relatively low, and the probability of difficulty in melting of more large-molecule binders during heating is also relatively low. During the cold pressing process of the positive electrode sheet, due to the strong binding effect of the large-molecule binder, the force between particles (such as positive electrode active material particles) is large, and the probability of brittle fracture of the positive electrode sheet caused by damage to the current collector is also relatively low. In this way, the positive electrode binder can have good binding performance, the amount of the positive electrode binder in the positive electrode material layer can be reduced, the coating of the positive electrode binder on the positive electrode active material can be reduced, so that the capacity of the positive electrode active material can be more fully exerted, thereby improving the energy density of the secondary battery. It also reduces the probability of brittle fracture of the positive electrode sheet, improves the manufacturing yield of the positive electrode sheet, and reduces the production cost of the secondary battery.

[0056] There is no particular limitation on the number-average molecular weight Mn of the positive electrode binder in this application, as long as the object of this application can be achieved. For example, 266,667 ≤ Mn ≤ 800,000.

[0057] There is no particular limitation on the type of the positive electrode binder in this application, as long as the object of this application can be achieved. For example, the positive electrode binder includes but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer or fluorinated acrylate resin. Or, the positive electrode binder includes but is not limited to at least one of vinylidene fluoride-hexafluoropropylene copolymer, polyvinyl alcohol, polyacrylonitrile, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM or fluororubber.

[0058] In some embodiments of the present application, based on the mass of the positive electrode material layer, the mass percentage content of the positive electrode conductive agent is W1%, the mass percentage content of the positive electrode binder is W2%, and the mass percentage content of the positive electrode active material is W3%. 0.2 ≤ W1 ≤ 2.0, 0.5 ≤ W2 ≤ 1.5, 96.5 ≤ W3 ≤ 99.1. Further, 0.5 ≤ W1 ≤ 1.0. Further, 0.7 ≤ W2 ≤ 1.5. Further, 97.7 ≤ W3 ≤ 98.8. For example, W1 is 0.2, 0.3, 0.4, 0.5, 0.7, 0.8, 0.9, 1.0, 1.2, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or any value between any two of the above numerical ranges. For example, W2 is 0.5, 0.6, 0.7, 0.8, 1.0, 1.1, 1.2, 1.3, 1.5 or any value between any two of the above numerical ranges. For example, W3 is 96.5, 96.7, 96.9, 97.1, 97.2, 97.3, 97.5, 97.7, 98.0, 98.2, 98.3, 98.5, 98.7, 98.8, 99.0, 99.1 or any value between any two of the above numerical ranges. Controlling the mass percentage content of the positive electrode conductive agent, the positive electrode binder, and the positive electrode active material within the above ranges is beneficial to preparing a positive electrode material layer with good adhesion, electrical conductivity, and high capacity, so that the secondary battery can have good charge and discharge performance and energy density, and also has a low production cost.

[0059] The present application does not particularly limit the type of the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material includes, but is not limited to, at least one of lithium cobaltate, lithium manganate, lithium nickelate, lithium nickel cobalt manganate, lithium nickel cobalt aluminate, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium-rich manganese-based material, or lithium titanate.

[0060] In some embodiments of the present application, based on the mass of the positive electrode material layer, the mass percentage content of the conductive carbon black is Y1%. 0.1 ≤ Y1 ≤ 1. For example, Y1 is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 or any value between any two of the above numerical ranges. Controlling the content of the conductive carbon black within the above range is beneficial to having a high coverage of the conductive carbon black particles on the surface of the positive electrode active material, being able to reduce the reaction activation energy, being beneficial to improving the conductive effect on the surface of the positive electrode active material particles, being beneficial to constructing a stable conductive network in the positive electrode material layer, and improving the ionic conductivity and electronic conductivity of the positive electrode plate, thereby improving the charge and discharge performance of the secondary battery.

[0061] In some embodiments of the present application, based on the mass of the positive electrode material layer, the mass percentage content of carbon nanotubes is Y2%, where 0.1 ≤ Y2 ≤ 0.5. For example, Y2 is 0.1, 0.2, 0.3, 0.4, 0.5, or any value between any two of the above numerical ranges. Controlling the content of carbon nanotubes within the above range is beneficial for carbon nanotubes to connect the particles of the positive electrode active material in series, maintain the network conductive network between the particles, enable a stable conductive network in the positive electrode material layer, and the positive electrode plate to have high ionic conductivity and electronic conductivity, thereby improving the charge-discharge performance of the secondary battery.

[0062] In some embodiments of the present application, based on the mass of the positive electrode material layer, the mass percentage content of flaky graphene is Y3%, where 0.1 ≤ Y3 ≤ 0.5. For example, Y3 is 0.1, 0.2, 0.3, 0.4, 0.5, or any value between any two of the above numerical ranges. Controlling the content of flaky graphene within the above range is beneficial for achieving surface contact between the particles of the positive electrode active material, increasing the contact sites, improving the conductive ability, enabling a stable and well-performing conductive network in the positive electrode material layer, and the positive electrode plate to have high ionic conductivity and electronic conductivity, thereby improving the charge-discharge performance of the secondary battery.

[0063] In some embodiments of the present application, the Dv99 of the positive electrode active material is D3 μm, and the relationship between H1 and D3 satisfies: 0.8 ≤ H1 / D3 ≤ 3.5. For example, H1 / D3 is 0.8, 0.9, 1.0, 1.2, 1.3, 1.5, 1.7, 1.9, 2.0, 2.1, 2.2, 2.4, 2.5, 2.7, 2.9, 3.0, 3.1, 3.2, 3.5, or any value between any two of the above numerical ranges. Controlling H1 / D3 within the above range is beneficial for the uniform distribution of the positive electrode active material in the positive electrode material layer, containing more positive electrode active material in the positive electrode material layer, providing a higher capacity for the secondary battery, and also beneficial for the positive electrode active material to have a higher specific surface area to contact the positive electrode conductive agent, so as to improve the ionic conductivity and electronic conductivity of the positive electrode plate, thereby enabling the secondary battery to have good charge-discharge performance and high energy density.

[0064] In some embodiments of the present application, 1.0 ≤ H1 / D3 ≤ 2.0. For example, H1 / D3 is 1.0, 1.2, 1.3, 1.5, 1.7, 1.9, 2.0, or any value between any two of the above numerical ranges. Controlling H1 / D3 within the above range is beneficial for the arrangement of the particles of the positive electrode active material in the positive electrode material layer, reducing the risk of crushing caused by the extrusion of the positive electrode active material particles, thereby being beneficial for further improving the charge-discharge performance and energy density of the secondary battery.

[0065] In some embodiments of the present application, 20 ≤ D3 ≤ 55. For example, D3 is 20, 22, 25, 27, 28, 30, 35, 37, 40, 42, 44, 46, 49, 50, 51, 53, 55, or any value between any two of the above numerical ranges. Controlling the particle size Dv99 of the positive electrode active material within the above range is beneficial for the positive electrode sheet to have a relatively high tap density, so as to improve the energy density of the secondary battery.

[0066] In the present application, the "particle size Dv99 of the positive electrode active material" refers to the particle size at which the cumulative volume of the positive electrode active material particles reaches 99% starting from the small particle size side in the particle size distribution based on volume.

[0067] The present application has no particular limitation on the method of controlling the particle size Dv99 of the positive electrode active material, as long as the purpose of the present application can be achieved. For example, it can be achieved by crushing, ball milling, and screening.

[0068] In some embodiments of the present application, the tap density of the positive electrode sheet is PD g / cm 3 , 3.8 ≤ PD ≤ 4.45. Preferably, 3.95 ≤ PD ≤ 4.25. For example, PD is 3.8, 3.85, 3.9, 3.95, 4.0, 4.1, 4.15, 4.20, 4.25, 4.30, 4.40, 4.45, or any value between any two of the above numerical ranges. Controlling the tap density of the positive electrode sheet within the above range is beneficial for having a relatively large number of positive electrode active material particles in the positive electrode material layer at the same thickness, providing a relatively high capacity for the secondary battery, and improving the energy density of the secondary battery.

[0069] The present application has no particular limitation on the method of controlling the tap density of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, it can be achieved by controlling the cold pressing pressure of the positive electrode sheet, the particle size of the positive electrode active material particles, etc.

[0070] In some embodiments of the present application, the positive electrode sheet further includes a bottom coating, which is disposed between the positive electrode current collector and the positive electrode material layer. The bottom coating includes inorganic particles and a bottom coating binder; the thickness of the bottom coating is H3 μm, and H3 and H1 satisfy: 10 ≤ H1 / H3 ≤ 110, 0.2 ≤ H3 ≤ 5.0. For example, the value of H1 / H3 is 10, 20, 30, 40, 45, 50, 61, 71, 80, 90, 100, 102, 110, or any value between any two of the above numerical ranges. For example, H3 is 0.2, 0.3, 0.4, 0.5, 0.7, 0.9, 1.0, 1.2, 1.3, 1.5, 1.8, 2.0, 2.1, 2.3, 2.5, 2.7, 3.0, 3.1, 3.5, 4.0, 4.5, 5.0, or any value between any two of the above numerical ranges. AsFigure 2 As shown, the positive electrode plate 100 includes a positive electrode current collector 101, a positive electrode material layer 10, and a bottom coating layer 20. The bottom coating layer 20 is disposed between the positive electrode current collector 101 and the positive electrode material layer 10. The thickness of the bottom coating layer 20 is shown as H3, and the thickness of the positive electrode material layer 10 is shown as H1. Further providing a bottom coating layer in the positive electrode plate and controlling the thickness of the bottom coating layer within the above range is beneficial to improving the adhesion of the positive electrode plate, reducing the probability of the positive electrode material layer peeling off from the positive electrode current collector, and is also beneficial to improving the hardness of the positive electrode plate and reducing the risk of the positive electrode plate being punctured. Thus, the secondary battery has good safety performance on the basis of having good charge and discharge performance and a high energy density.

[0071] In some embodiments of the present application, 0.5 ≤ H3 ≤ 2.5. For example, H3 is 0.5, 0.7, 0.9, 1.0, 1.2, 1.3, 1.5, 1.8, 2.0, 2.1, 2.3, 2.5 or any value between any two of the above numerical ranges. Controlling the thickness of the bottom coating layer within the above range is beneficial to reducing the thickness of the positive electrode plate on the basis of improving the adhesion and hardness of the positive electrode plate, so as to reduce the probability of the energy density of the secondary battery being lost due to the increase in the thickness of the positive electrode plate. Thus, the secondary battery can further improve its energy density on the basis of having good charge and discharge performance and safety performance.

[0072] The present application does not particularly limit the types of inorganic particles and bottom coating layer binders, as long as the objects of the present application can be achieved. For example, the inorganic particles include but are not limited to at least one of alumina, boehmite, titanium dioxide, silicon dioxide, zirconium dioxide, tin dioxide, magnesium hydroxide, magnesium oxide, zinc oxide, barium sulfate, boron nitride, or aluminum nitride. The bottom coating layer binders include but are not limited to at least one of polyvinylidene fluoride, polymethyl acrylate, polyvinyl alcohol (PVA), polyacrylic acid (PAA), carboxymethyl cellulose, styrene-butadiene rubber (SBR), or polymethyl methacrylate. The present application does not particularly limit the particle size of the inorganic particles, as long as the objects of the present application can be achieved. The present application does not particularly limit the molecular weight of the bottom coating layer binders, as long as the objects of the present application can be achieved. The present application does not particularly limit the mass percentage content of the inorganic particles and the bottom coating layer binders in the bottom coating layer, as long as the objects of the present application can be achieved. For example, based on the mass of the bottom coating layer, the mass percentage content of the inorganic particles is 85% to 95%, and the mass percentage content of the bottom coating layer binders is 5% to 15%.

[0073] The present application does not particularly limit the positive electrode current collector, as long as the objects of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil or aluminum alloy foil, etc. In the present application, the thickness of the positive electrode current collector is not particularly limited, as long as the objects of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm.

[0074] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam or copper foam, etc. The negative electrode material layer of the present application contains a negative electrode active material. The present application has no particular limitation on the type of the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO x (0 < x < 2), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, lithium titanate with a spinel structure Li4Ti5O 12 , Li-Al alloy or metallic lithium, etc. At least one of them. In the present application, there is no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 6 μm to 10 μm. Optionally, the negative electrode material layer may further include at least one of a negative electrode conductive agent, a dispersant or a negative electrode binder. The present application has no particular limitation on the types of the negative electrode conductive agent, the dispersant and the negative electrode binder in the negative electrode material layer, as long as the purpose of the present application can be achieved. The present application has no particular limitation on the mass ratio of the negative electrode active material, the negative electrode conductive agent, the dispersant and the negative electrode binder in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the mass ratio of the negative electrode active material, the negative electrode conductive agent, the dispersant and the negative electrode binder in the negative electrode material layer is (96 to 98):(0.5 to 2):(0 to 1.5):(1.0 to 1.9).

[0075] The present application has no particular limitation on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include, but is not limited to, at least one of polyolefins (PO) mainly composed of polyethylene (PE) and polypropylene (PP), polyester (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of the separator may include at least one of a woven film, a non-woven film, a microporous film, a composite film, a calendared film or a spun film. The present application has no particular limitation on the thickness of the separator, as long as the purpose of the present application can be achieved.

[0076] In one embodiment of the present application, the secondary battery includes an electrolyte. The present application has no particular limitation on the type of the electrolyte, and those skilled in the art can select a well-known electrolyte in the art according to actual needs, as long as the purpose of the present application can be achieved.

[0077] In an embodiment of the present application, the secondary battery includes a packaging bag for accommodating a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. The present application does not particularly limit the type of the packaging bag, and those skilled in the art can select a packaging bag well-known in the art according to actual needs as long as the purpose of the present application can be achieved.

[0078] The secondary battery of the present application is not particularly limited, and it may include any device that undergoes an electrochemical reaction. For example, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0079] The present application does not particularly limit the preparation method of the positive electrode sheet, and the preparation methods well-known in the art can be adopted as long as the purpose of the present application can be achieved. For example, in some embodiments of the present application, the preparation method of the positive electrode sheet includes but is not limited to the following steps: (1) uniformly mixing the positive electrode conductive agent, the positive electrode binder, and the positive electrode active material in the contents of the present application, adding a solvent, and stirring evenly to obtain a positive electrode slurry; (2) uniformly coating the positive electrode slurry on one surface of the positive electrode current collector, and drying and cold pressing to form a positive electrode sheet with a positive electrode material layer disposed on one side. In another embodiment, the preparation method of the positive electrode sheet includes the following steps: (1) uniformly mixing the positive electrode conductive agent, the positive electrode binder, and the positive electrode active material in the contents of the present application, adding a solvent, and stirring evenly to obtain a positive electrode slurry; (2) uniformly coating the positive electrode slurry on one surface of the positive electrode current collector, and drying to form a positive electrode material layer; (3) repeating step (2) on the other surface of the positive electrode current collector, and cold pressing and slitting to obtain a positive electrode sheet with positive electrode material layers disposed on both sides. For example, in some other embodiments of the present application, the preparation method of the positive electrode sheet includes but is not limited to the following steps: (1) uniformly mixing the positive electrode conductive agent, the positive electrode binder, and the positive electrode active material in the contents of the present application, adding a solvent, and stirring evenly to obtain a positive electrode slurry; uniformly mixing the inorganic particles and the bottom coating binder, adding a solvent, and stirring evenly to obtain a bottom coating slurry; (2) uniformly coating the bottom coating slurry on one surface of the positive electrode current collector, drying to form a bottom coating, and uniformly coating the positive electrode slurry on the surface of the bottom coating away from the positive electrode current collector, and drying and cold pressing to form a positive electrode sheet with a bottom coating and a positive electrode material layer disposed on one side. In another embodiment, the preparation method of the positive electrode sheet includes the following steps: (1) uniformly mixing the positive electrode conductive agent, the positive electrode binder, and the positive electrode active material in the contents of the present application, adding a solvent, and stirring evenly to obtain a positive electrode slurry; uniformly mixing the inorganic particles and the bottom coating binder, adding a solvent, and stirring evenly to obtain a bottom coating slurry; (2) uniformly coating the bottom coating slurry on one surface of the positive electrode current collector, drying to form a bottom coating, and uniformly coating the positive electrode slurry on the surface of the bottom coating away from the positive electrode current collector, and drying and cold pressing to form a positive electrode sheet with a bottom coating and a positive electrode material layer disposed on one side; (3) repeating step (2) on the other surface of the positive electrode current collector, and cold pressing and slitting to obtain a positive electrode sheet with bottom coatings and positive electrode material layers disposed on both sides. The present application does not particularly limit the solid content of the positive electrode slurry and the bottom coating slurry as long as the purpose of the present application can be achieved. For example, the solid content of the positive electrode slurry is 50 wt% to 80 wt%, and the solid content of the bottom coating slurry is 20 wt% to 50 wt%. The present application does not particularly limit the type of the above solvent as long as the purpose of the present application can be achieved. For example, the solvent may include but is not limited to N-methylpyrrolidone (NMP) or deionized water.

[0080] The preparation method of the secondary battery of the present application is not particularly limited, and a preparation method well-known in the art can be selected as long as the object of the present application can be achieved. For example, the preparation method of the secondary battery includes but is not limited to the following steps: stacking a separator, a positive electrode sheet, a separator, and a negative electrode sheet in sequence, and winding, folding, etc. as needed to obtain a wound electrode assembly, placing the electrode assembly in a packaging bag, injecting an electrolyte into the packaging bag and sealing it to obtain a secondary battery; or, stacking a separator, a positive electrode sheet, a separator, and a negative electrode sheet in sequence, and then fixing the four corners of the entire laminated structure to obtain a laminated electrode assembly, placing the electrode assembly in a packaging bag, injecting an electrolyte into the packaging bag and sealing it to obtain a secondary battery.

[0081] The second aspect of the present application provides an electronic device, which includes the secondary battery described in any of the foregoing embodiments. Therefore, the electronic device has good use performance.

[0082] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. For example, the electronic device may include but is not limited to: laptop computer, pen input computer, mobile computer, e-book player, portable phone, portable fax machine, portable copier, portable printer, head-mounted stereo headphones, video recorder, liquid crystal TV, hand-held cleaner, portable CD player, mini disc, transceiver, electronic notepad, calculator, memory card, portable recorder, radio, backup power supply, motor, car, motorcycle, moped, bicycle, lighting fixture, toy, game console, clock, power tool, flashlight, camera, large household battery, and lithium-ion capacitor.

[0083] Examples

[0084] Hereinafter, examples and comparative examples are given to more specifically illustrate the embodiments of the present application. Various tests and evaluations are carried out according to the following methods.

[0085] Testing methods and equipment:

[0086] Sampling method of the positive electrode sheet and the negative electrode sheet:

[0087] After discharging each of the lithium-ion batteries of the examples and comparative examples at a constant current of 0.2C to 3.0V, they were disassembled to obtain a positive electrode sheet and a negative electrode sheet. The surface of the positive electrode sheet was cleaned with dimethyl carbonate (DMC) to obtain a positive electrode sheet sample. The surface of the negative electrode sheet was washed with deionized water until there was no obvious separator coating on the surface of the negative electrode sheet to obtain a negative electrode sheet sample.

[0088] Measurement of thickness:

[0089] The thicknesses of the positive electrode material layer, the bottom coating layer, and the negative electrode material layer were measured by a microscopy method.

[0090] (a) Test of the thickness of the positive electrode material layer and the bottom coating layer:

[0091] Use a scanning electron microscope (SEM) to observe the cross-section of the positive electrode sheet, and directly measure the thickness of the positive electrode material layer and the bottom coating layer.

[0092] Steps: (1) Prepare the sample: Cut the positive electrode sheet into thin slices along its thickness direction to obtain a clear cross-section. (2) Observe: Use SEM to observe the cross-section and find the boundary between the positive electrode material layer and the bottom coating layer. (3) Measure: Use the measurement function of SEM to directly measure the thickness of the positive electrode material layer and the bottom coating layer. When measuring the thickness, randomly measure three positions respectively and take the average value as the final thickness. The thickness in this application refers to the thickness of one side.

[0093] (b) Test of the thickness of the negative electrode material layer: The thickness of the negative electrode material layer is tested by the method in (a).

[0094] Test of the coating surface density:

[0095] Obtain the positive electrode sheet and the negative electrode sheet according to the above sampling method. The test is carried out according to the following test steps:

[0096] (1) Punch the positive electrode sheet into small round pieces with a radius of R (area 1540.25 mm2), then weigh the weight as m1. Scrape off the positive electrode material layers on both surfaces of the positive electrode sheet, and weigh the weight of the positive electrode current collector or the positive electrode current collector and the bottom coating layer as m2. Then the coating surface density C1 of the positive electrode sheet = (m1 - m2) / (2πR 2 ), and the unit is mg / cm 2 .;

[0097] (2) Punch the negative electrode sheet into small round pieces with a radius of R, then weigh the weight as m3. Scrape off the negative electrode material layers on both surfaces of the negative electrode sheet, and weigh the weight of the negative electrode current collector as m4. Then the coating surface density C2 of the negative electrode sheet = (m3 - m4) / (2πR 2 ), and the unit is mg / cm 2 .

[0098] Test of the specific surface area of conductive carbon black:

[0099] Use a specific surface area analyzer (Micromeritics Instrument Corporation, USA, TristarⅡ3020M) to measure the specific surface area of the conductive carbon black particles in each example and comparative example by the nitrogen adsorption method. Among them, the specific test is carried out according to the national standard GB / T19587-2017 "Determination of specific surface area of solid materials by gas adsorption BET method".

[0100] Test of the particle size Dv50 of conductive carbon black:

[0101] The particle size test curve of conductive carbon black was measured using a Malvern particle size analyzer (model MasterSizer 2000). The particle size Dv50 of conductive carbon black was obtained by analyzing the curve. Add 0.02 g of conductive carbon black to a 50 mL beaker, add 20 mL of dispersant ethanol, and ultrasonicate for 30 min in a 120 W ultrasonic cleaner to obtain a sample dispersion. Use the Malvern particle size analyzer to test the above sample dispersion. First, clean the injection system with water. Select a refractive index of 1.8, an absorption rate of 1, the name of the dispersant as water, the refractive index of the dispersant as 1.333, and the analysis model as general spherical. When the test background light intensity < 200 or the laser intensity > 70%, add the sample until the obscuration reaches the range of 8% to 12%, stop adding the sample, let it stand for 30 s, and after observing that the obscuration remains stable, conduct the test to obtain the particle size distribution diagram. Dv50 is the particle size that reaches 50% of the volume cumulative from the small particle size side in the particle size distribution based on volume.

[0102] Measurement of size parameters of flaky graphene and carbon nanotubes:

[0103] (1) Take the positive electrode plate and obtain the cross-section of the positive electrode material layer on the positive electrode plate by brittle fracture with liquid nitrogen.

[0104] (2) Observe the flaky graphene and carbon nanotubes in the cross-section obtained in (1) under SEM. Measure the diameter and length of the carbon nanotubes at a magnification of 30K times; measure the flake diameter of the flaky graphene at a magnification of 30K times. The above size parameters are obtained by testing 10 different positions in the positive electrode material layer, measuring 30 values for each parameter, and then calculating the average value. Among them, the units of the length and diameter of the carbon nanotubes are nm, and the unit of the flake diameter of the flaky graphene is μm.

[0105] Measurement of the molecular weight of the positive electrode binder:

[0106] The test was carried out using the method of testing the molecular weight of polymers by ultra-high performance polymer chromatography. Specifically, referring to the national standard: GB / T21863-2008 Gel Permeation Chromatography (GPC), using tetrahydrofuran as the eluent; use an ultra-high performance polymer chromatograph (instrument model: ACQUITY APC) to test the weight-average molecular weight Mw and number-average molecular weight Mn of the positive electrode binder, and calculate its molecular weight distribution Mw / Mn.

[0107] Measurement of the particle size Dv99 of the positive electrode active material:

[0108] (1) Take the positive electrode plate and heat it to 600 °C at a rate of 10 °C / min in a muffle furnace under a nitrogen atmosphere and calcine for 180 min.

[0109] Take out the residual substance;

[0110] (2) Scrape the powder off the current collector to obtain the positive electrode active material;

[0111] (3) The method for testing the particle size of the positive electrode active material is as follows:

[0112] Use a Malvern particle size analyzer (model MasterSizer 2000) to measure the particle size of the positive electrode active material. Scrape the positive electrode material layer on the surface of the positive electrode plate, and after cleaning, centrifuging, and drying with DMC, obtain the positive electrode active material. Add 0.02 g of the positive electrode active material to a 50 mL clean beaker, add 20 mL of the dispersant ethanol, and ultrasonicate in a 120 W ultrasonic cleaner for 30 min to completely disperse the positive electrode active material in ethanol to obtain a sample dispersion. Use the Malvern particle size analyzer to test the above sample dispersion. First, clean the injection system with water, select a refractive index of 1.8, an absorption rate of 1, the name of the dispersant as water, the refractive index of the dispersant as 1.333, the analysis model as the general sphere. When the test background light intensity < 200 or the laser intensity > 70%, add the sample until the obscuration reaches the range of 8% to 12%, stop adding the sample, let it stand for 30 s, and after observing that the obscuration remains stable, conduct the test to obtain the particle size distribution diagram. Dv99 is the particle size that reaches 99% of the volume cumulative from the small particle size side in the particle size distribution based on volume.

[0113] Test of the compaction density of the positive electrode plate:

[0114] Use a punching machine to punch a small round piece with an area of S on the positive electrode plate, weigh its mass as M1, and measure its thickness as T1 with a micrometer; use the same punching machine to punch the positive electrode current collector and the bottom coating with the same area S, and weigh their mass M2, and measure their thickness as T2 with a micrometer; the compaction density of the positive electrode plate is: (M1 - M2) / (T1 - T2) / S.

[0115] Test of the charging time:

[0116] In an environment of (25 ± 3)°C, the lithium-ion battery is charged at a constant current of 1.0C until 4.53V, and then changed to a constant voltage of 4.53V until the cut-off current of 0.05C, obtaining the state of the lithium-ion battery as 100% SOC (state of charge), and the charging time to reach this state is the 100% SOC full charge charging time.

[0117] Test of the capacity retention rate:

[0118] At 45 °C, the lithium-ion battery is charged at a constant current of 0.5C to 4.53V, and finally charged at a constant voltage of 4.5V to 0.025C, then left standing for 30 min, and discharged at a constant current of 0.2C to 3.0V. Record the discharge capacity as D0; after standing for 5 min, the lithium-ion battery is charged at a constant current of 0.5C to 4.53V and then charged at a constant voltage of 4.53V to 0.025C, left standing for 30 min, and discharged at a constant current of 1C to 3.0V. Record the discharge capacity as D1. Then the retention rate (%) of the 1C discharge capacity = D1 / D0 × 100%.

[0119] Measurement of energy density:

[0120] First, measure the dimensions of the lithium-ion battery to obtain the thickness T, width W, and length L, and calculate the volume V through the following formula: V = T × W × L.

[0121] Then, charge the lithium-ion battery according to the following operation process and then discharge it to obtain the discharge capacity E of the lithium-ion battery:

[0122] Charging: Charge at a constant current of 2C to 4.3V and then charge at a constant voltage of 4.3V to 0.05C;

[0123] Discharging: Discharge at a constant current of 0.5C to 2.5V to obtain the discharge capacity E.

[0124] The energy density (ED) of the lithium-ion battery can be calculated through the following formula: ED (Wh / cm 3 ) = E / V.

[0125] Example 1-1

[0126] <Preparation of the positive electrode sheet>

[0127] Mix the positive electrode conductive agents, carbon black, carbon nanotubes, and flaky graphene with the positive electrode binder polyvinylidene fluoride (PVDF), add N-methylpyrrolidone (NMP), and formulate a conductive adhesive solution with a solid content of 7 wt%. Then add the positive electrode active material lithium cobalt oxide, and continue to stir under the action of a vacuum mixer until the system becomes homogeneous to obtain a slurry with a solid content of 75 wt%. Uniformly coat the positive electrode slurry on one surface of a positive electrode current collector aluminum foil with a thickness of 10 μm, and dry it at 120 °C to obtain a positive electrode sheet with a single-sided coated positive electrode material layer. Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coated positive electrode material layer. After drying at 120 °C, cold press it, and then cut the sheet, weld the tab, and obtain a positive electrode sheet with a specification of 74 mm × 867 mm for use.

[0128] Based on the mass of the positive electrode material layer, the mass percentage contents of the positive electrode active material, binder, and conductive agent are shown in Table 2.

[0129] <Preparation of Negative Electrode Plate>

[0130] Mix artificial graphite as the negative electrode active material, styrene-butadiene rubber as the binder, and acetylene black as the conductive agent in a mass ratio of 97.4:1.4:1.2. Add deionized water as the solvent to formulate a slurry with a solid content of 45 wt%. After stirring evenly with a vacuum mixer, the negative electrode slurry is obtained. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6 μm and dried at 120 °C to obtain a negative electrode plate with a single-sided coated negative electrode material layer. Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode plate with a double-sided coated negative electrode material layer. After drying at 120 °C, it is cold-pressed, and then cut into pieces and the electrode tabs are welded to obtain a negative electrode plate with a specification of 78 mm × 875 mm for standby.

[0131] <Preparation of Electrolyte>

[0132] In an environment with a water content of less than 10 ppm, mix ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) in a mass ratio of 1:1:1 to obtain an organic solvent. Then add lithium salt LiPF6 to the organic solvent and mix evenly to obtain the electrolyte. Among them, based on the mass of the electrolyte, the mass percentage content of the lithium salt is 12.5%, and the rest is the organic solvent.

[0133] <Separator>

[0134] Use a porous polyethylene film with a thickness of 7 μm (provided by Celgard) as the separator.

[0135] <Preparation of Lithium-Ion Battery>

[0136] Stack the positive electrode plate, separator, and negative electrode plate prepared above in sequence, with the separator in the middle of the positive electrode plate and the negative electrode plate to play a role in isolation, and wind to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the moisture is removed at 80 °C, and the prepared electrolyte is injected. After vacuum packaging, standing, forming, degassing, trimming and other processes, a lithium-ion battery is obtained.

[0137] Examples 1-2 to Examples 1-33

[0138] Except for adjusting the relevant preparation parameters according to Table 1, the rest are the same as Example 1-1.

[0139] Examples 2-1 to Examples 2-18

[0140] Except for adjusting the relevant preparation parameters according to Table 2, the rest are the same as Example 1-1.

[0141] Examples 3-1 to Examples 3-8

[0142] Except for regulating the relevant preparation parameters according to Table 3, the rest are the same as in Example 1-1.

[0143] Examples 4-1 to 4-14

[0144] Except for regulating the relevant preparation parameters according to Table 4, the rest are the same as in Example 1-1.

[0145] Example 4-15

[0146] <Preparation of the positive electrode sheet>

[0147] Select the same positive electrode slurry as in Example 1-1.

[0148] Mix inorganic particle boehmite and the bottom coating binder polyacrylic acid (weight average molecular weight 400,000), add deionized water as a solvent, and stir evenly to form a bottom coating slurry with a solid content of 40 wt%.

[0149] Uniformly coat the bottom coating slurry on one surface of a 10-μm-thick positive electrode current collector aluminum foil, dry it at 120 °C to form a bottom coating, uniformly coat the positive electrode slurry on the surface of the bottom coating away from the aluminum foil, and dry it at 120 °C to obtain a positive electrode sheet with a single-sided coated bottom coating and a positive electrode material layer. Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coated bottom coating and a positive electrode material layer. Cold press, and then cut, weld the tab to obtain a positive electrode sheet with a specification of 74 mm × 867 mm for standby.

[0150] The rest are the same as in Example 4-5.

[0151] Examples 4-16 to 4-22

[0152] Except for regulating the relevant preparation parameters according to Table 4, the rest are the same as in Example 4-15.

[0153] Comparative Examples 1 to 8

[0154] Except for regulating the relevant preparation parameters according to Table 1, the rest are the same as in Example 1-1.

[0155] The preparation parameters and performance data of each example and comparative example are shown in Tables 1 to 4.

[0156] Table 1

[0157]

[0158]

[0159] Note: The "\ " in Table 1 indicates no corresponding parameter.

[0160] As can be seen from Examples 1-1 to 1-33 and Comparative Examples 1 to 8, when the thickness of the positive electrode material layer in the secondary battery of the present application is within the scope of the present application, at least one of conductive carbon black with a Dv50 particle size within the scope of the present application and carbon nanotubes or flaky graphene is used in combination, the secondary battery has a shorter charging time and a higher discharge capacity retention rate, indicating that the secondary battery of the example has better charge and discharge performance, and the secondary battery has a higher energy density. For the secondary battery of the comparative example, the thickness of the positive electrode material layer is outside the scope of the present application, the Dv50 particle size of the conductive carbon black is outside the scope of the present application, or it does not contain at least one combination of conductive carbon black and carbon nanotubes or flaky graphene. The secondary battery of the comparative example has a longer charging time, or a lower discharge capacity retention rate, or a smaller energy density.

[0161] The thickness H1 of the positive electrode material layer, the coating surface density C1 of the positive electrode material layer, the thickness H2 of the negative electrode material layer, and the coating surface density C2 of the negative electrode material layer usually affect the charge and discharge performance and energy density of the secondary battery. As can be seen from Examples 1-1 to 1-7, Comparative Examples 3 and 4, for the secondary battery with the thickness H1 of the positive electrode material layer, the coating surface density C1 of the positive electrode material layer, the thickness H2 of the negative electrode material layer, and the coating surface density C2 of the negative electrode material layer within the scope of the present application, it has a shorter charging time, a higher discharge capacity retention rate, and an energy density, indicating that the secondary battery has good charge and discharge performance and a higher energy density.

[0162] The specific surface area and Dv50 particle size of the conductive carbon black usually affect the charge and discharge performance and energy density of the secondary battery. As can be seen from Examples 1-1, 1-8 to 1-19, Comparative Examples 1 and 2, for the secondary battery with the specific surface area and Dv50 particle size of the conductive carbon black within the scope of the present application, it has a shorter charging time, a higher discharge capacity retention rate, and an energy density, indicating that the secondary battery has good charge and discharge performance and a higher energy density.

[0163] The diameter, length, and aspect ratio of the carbon nanotubes usually affect the charge and discharge performance and energy density of the secondary battery. As can be seen from Examples 1-1, 1-20 to 1-29, for the secondary battery with the diameter, length, and aspect ratio of the carbon nanotubes within the scope of the present application, it has a shorter charging time, a higher discharge capacity retention rate, and an energy density, indicating that the secondary battery has good charge and discharge performance and a higher energy density.

[0164] The sheet diameter of flaky graphene usually affects the charge-discharge performance and energy density of secondary batteries. As can be seen from Example 1-1, Examples 1-30 to 1-33, the secondary batteries using flaky graphene with a sheet diameter within the scope of this application have a shorter charging time, a higher discharge capacity retention rate, and energy density, indicating that the secondary batteries have good charge-discharge performance and high energy density.

[0165] Table 2

[0166]

[0167]

[0168] Note: The "\ " in Table 2 indicates no corresponding parameter.

[0169] The content of the positive electrode conductive agent and the respective contents of conductive carbon black, carbon nanotubes, and flaky graphene usually affect the charge-discharge performance and energy density of secondary batteries. As can be seen from Example 1-1, Examples 2-1 to 2-11, the secondary batteries using the content of the positive electrode conductive agent and the respective contents of conductive carbon black, carbon nanotubes, and flaky graphene within the scope of this application have a shorter charging time, a higher discharge capacity retention rate, and energy density, indicating that the secondary batteries have good charge-discharge performance and high energy density.

[0170] The contents of the positive electrode conductive agent, the positive electrode active material, and the positive electrode binder usually affect the charge-discharge performance and energy density of secondary batteries. As can be seen from Example 1-1, Examples 2-3 to 2-18, the secondary batteries using the contents of the positive electrode conductive agent, the positive electrode active material, and the positive electrode binder within the scope of this application have a shorter charging time, a higher discharge capacity retention rate, and energy density, indicating that the secondary batteries have good charge-discharge performance and high energy density.

[0171] Table 3

[0172]

[0173] The weight-average molecular weight Mw of the positive electrode binder and its ratio Mw / Mn to the number-average molecular weight Mn usually affect the charge-discharge performance and energy density of secondary batteries. As can be seen from Example 1-1, Examples 3-1 to 3-8, the secondary batteries using the weight-average molecular weight Mw of the positive electrode binder and its ratio Mw / Mn to the number-average molecular weight Mn within the scope of this application have a shorter charging time, a higher discharge capacity retention rate, and energy density, indicating that the secondary batteries have good charge-discharge performance and high energy density.

[0174] Table 4

[0175]

[0176] Note: The "\\" in Table 4 indicates no corresponding parameter.

[0177] The particle size Dv99 of the positive electrode active material and the ratio H1 / D3 between it and the thickness of the positive electrode material layer usually affect the charge and discharge performance and energy density of the secondary battery. It can be seen from Examples 1-1, 4-1 to 4-8 that for a secondary battery using a positive electrode active material with a particle size Dv99 and a ratio H1 / D3 between it and the thickness of the positive electrode material layer within the scope of this application, it has a shorter charging time, a higher discharge capacity retention rate, and energy density, indicating that the secondary battery has good charge and discharge performance and a high energy density.

[0178] The tap density PD of the positive electrode sheet usually affects the charge and discharge performance and energy density of the secondary battery. It can be seen from Examples 1-1, 4-9 to 4-14 that for a secondary battery using a positive electrode sheet with a tap density within the scope of this application, it has a shorter charging time, a higher discharge capacity retention rate, and energy density, indicating that the secondary battery has good charge and discharge performance and a high energy density.

[0179] When a bottom coating is further provided in the positive electrode sheet, the thickness H3 of the bottom coating and the value of the ratio H1 / H3 between it and the thickness of the positive electrode material layer usually affect the charge and discharge performance and energy density of the secondary battery. It can be seen from Examples 1-1, 4-15 to 4-22 that for a secondary battery using a bottom coating with a thickness H3 and a ratio H1 / H3 between it and the thickness of the positive electrode material layer within the scope of this application, it has a shorter charging time, a higher discharge capacity retention rate, and energy density, indicating that the secondary battery has good charge and discharge performance and a high energy density.

[0180] It should be noted that in this article, the term "comprising", "including" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0181] Each embodiment in this specification is described in a related manner. For the same or similar parts between each embodiment, reference can be made to each other. The key point of each embodiment is to illustrate the differences from other embodiments.

[0182] The above are only the preferred embodiments of this application, and are not intended to limit this application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of this application shall be included within the scope of protection of this application.

Claims

1. A secondary battery, comprising a positive electrode sheet, a separator and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, and the negative electrode sheet comprises the negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; The thickness of the positive electrode material layer is H1μm, 22≤H1≤110; the positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductor, the positive electrode conductor includes conductive carbon black, and at least one of carbon nanotubes or flaky graphene; the particle size Dv50 of the conductive carbon black is D1μm, 0.5≤D1≤20.

2. The secondary battery according to claim 1, wherein The specific surface area of ​​the conductive carbon black is Sm 2 / g, 200≤S≤2100.

3. The secondary battery according to claim 1 or 2, wherein: The secondary battery satisfies at least one of the following characteristics: (1) The specific surface area of ​​the conductive carbon black is Sm 2 / g, 600≤S≤1800; (2)1.5≤D1≤10。 4. The secondary battery according to claim 1, wherein The secondary battery satisfies at least one of the following characteristics: (1) The specific surface area of ​​the conductive carbon black is Sm 2 / g, 1200≤S≤1800; (2) The thickness of the positive electrode material layer is H1 μm, 45≤H1≤100.

5. The secondary battery according to claim 1, wherein The coating surface density of the positive electrode material layer is C1 mg / cm 2 , 10≤C1≤55.

6. The secondary battery according to claim 1, wherein The negative electrode plate satisfies at least one of the following characteristics: (1) The thickness of the negative electrode material layer is H2 μm, 10≤H2≤140; (2) The coating surface density of the negative electrode material layer is C2 mg / cm 2 , 2.5≤C2≤35.

7. The secondary battery according to claim 1, wherein The carbon nanotubes satisfy at least one of the following characteristics: (1) The length of the carbon nanotube is L1 nm, 100≤L1≤6000; (2) The diameter of the carbon nanotube is D2 nm, 8≤D2≤18; (3) The aspect ratio L1 / D2 of the carbon nanotubes satisfies: 25≤L1 / D2≤300.

8. The secondary battery according to claim 1, wherein The flake graphene has a diameter of 5 μm to 15 μm.

9. The secondary battery according to claim 1, wherein The weight average molecular weight of the positive electrode binder is Mw, the number average molecular weight of the positive electrode binder is Mn, and Mw and Mn satisfy: 1.5≤Mw / Mn≤3, 800000≤Mw≤1200000.

10. The secondary battery according to claim 1, wherein Based on the mass of the positive electrode material layer, the mass percentage of the positive electrode conductor is W1%, the mass percentage of the positive electrode binder is W2%, the mass percentage of the positive electrode active material is W3%, 0.2≤W1≤2.0, 0.5≤W2≤1.5, 96.5≤W3≤99.

1.

11. The secondary battery according to claim 10, wherein The secondary battery satisfies at least one of the following characteristics: (1)0.5≤W1≤1.0; (2)0.7≤W2≤1.5; (3)97.7≤W3≤98.8。 12. The secondary battery according to claim 10, wherein The positive electrode conductive agent satisfies at least one of the following characteristics: (1) Based on the mass of the positive electrode material layer, the mass percentage of the conductive carbon black is Y1%, 0.1≤Y1≤1; (2) Based on the mass of the positive electrode material layer, the mass percentage of the carbon nanotubes is Y2%, 0.1≤Y2≤0.5; (3) Based on the mass of the positive electrode material layer, the mass percentage of the flaky graphene is Y3%, 0.1≤Y3≤0.

5.

13. The secondary battery according to any one of claims 1 to 12, wherein: The thickness of the positive electrode material layer is 70 μm to 100 μm.

14. The secondary battery according to claim 1, wherein The particle size Dv99 of the positive electrode active material is D3 μm, and H1 and D3 satisfy the following: 0.8≤H1 / D3≤3.

5.

15. The secondary battery according to claim 14, wherein The positive electrode sheet satisfies at least one of the following characteristics: (1) 1.0≤H1 / D3≤2.0; (2)20≤D3≤55; (3) The compaction density of the positive electrode sheet is PD g / cm 3 , 3.8≤PD≤4.

45.

16. The secondary battery according to claim 1, wherein The positive electrode sheet further includes a primer layer, which is disposed between the positive electrode current collector and the positive electrode material layer, and includes inorganic particles and a primer binder; The thickness of the primer layer is H3 μm, and H3 and H1 satisfy: 10≤H1 / H3≤110, 0.2≤H3≤5.

0.

17. The secondary battery according to claim 16, wherein 0.5≤H3≤2.5。 18. An electronic device, wherein: The electronic device includes the secondary battery according to any one of claims 1 to 17.